2016
DOI: 10.3397/1/376402
|View full text |Cite
|
Sign up to set email alerts
|

Development of noise controls for longwall shearer cutting drums

Abstract: Noise-induced hearing loss is the second most pervasive disease in the mining industry. The exposure of miners to noise levels above the permissible exposure level results in hearing loss of approximately 80% of coal miners by retirement age. In addition, between 2002 and 2011, approximately 48% of longwall shearer operators were overexposed in coal mines in the United States. Previous research identified the two rotating cutting drums used by the longwall shearer to extract coal as the most significant sound-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…The prediction results of the ISO 1999:2013 model were consistent with the development law of hearing loss. These jobs (excavation worker, mill operator, and crusher operator) were likely to have a high incidence of occupational hearing loss, which was consistent with the high noise exposure positions identified in other studies ( 20 , 21 ).…”
Section: Discussionsupporting
confidence: 88%
“…The prediction results of the ISO 1999:2013 model were consistent with the development law of hearing loss. These jobs (excavation worker, mill operator, and crusher operator) were likely to have a high incidence of occupational hearing loss, which was consistent with the high noise exposure positions identified in other studies ( 20 , 21 ).…”
Section: Discussionsupporting
confidence: 88%
“…In addition to regulatory measures, successful noise‐reducing equipment and methods have been developed/identified within Mining. Engineering controls, such as modified tail sections of continuous mining machines, noise control packages for vibrating screens, applying noise barriers and absorptive treatments within talc processing plants, drill bit isolators for roof bolting machines, structural modifications to cutting drums of longwall shearers, and noise control packages for vibrating screens, have shown to decrease noise emitted by equipment, while also maintaining durability. A 2009 study found that new‐style haul truck cabs used in limestone mines were significantly quieter (65.1 dBA) than old‐style (84.8 dBA) and retro‐fitted cabs (84.9 dBA) with the windows closed .…”
Section: Discussionmentioning
confidence: 99%
“…Recently developed engineering controls have shown great promise in reducing equipment noise within mining . Incorporation and continued development of these technologies, both in Mining and OGE, is critical for reducing worker exposures, in addition to employing effective administrative controls.…”
Section: Discussionmentioning
confidence: 99%
“…Among the main ecological hazards in mines, the impact of noise on occupational health is the secondmost important hazard after dust [27]. If miners are exposed to 85 dBA of high-intensity noise for long periods of time without protective equipment, they may lose their hearing and cause permanent occupational deafness [28].…”
Section: Revealsmentioning
confidence: 99%